Recent trends in the patterns of dyslipidemia and management strategy in newly diagnosed patients of type 2 diabetes mellitus-2 - Patel, Dixit; Dave, Nilanj; Kalkoti, Vinob; Nayak, Mithilesh (International Journal of Advances in Medicine, 2022)
Background: Objective of the study was to evaluate the patterns of dyslipidaemia in newly diagnosed type 2 diabetes mellitus-2 (T2DM) patients and to understand the initial management options utilised by the treating physician. Methods: The real world, retrospective, observational REcent trends in the patterns of dyslipidemia and Management strategy in newly diAgnosed Patients of type 2 diabetes mellitus-2 (REMAP-2) study was conducted at various centers including hospitals, clinics, and health care institutes across India between Apr-2021 and Mar-2022. Clinicians at the respective center captured the data in REMAP-2 study data capture form. Dyslipidemia was considered as: total cholesterol >200 mg/dl, low density lipoprotein cholesterol (LDL-C) >100 mg/dl, high density lipoprotein cholesterol (HDL-C) <40 mg/dl, or triglyceride >150 mg/dl. Results: Of 9605 newly diagnosed T2DM patients with dyslipidemia, 68.94% (n=6622) had mixed dyslipidemia. The mean age was 53.8 years. Majority of the patients were males (63.3%), had family history of diabetes (52.5%), physical activity category of ‘not very active’ or ‘lightly active’ (79.33%), and were overweight or obese (58.9%). About 25.9% of the patients were smokers. Hypertension (72.33%) was the most common comorbidity followed by coronary artery disease (23.44%). The mean glycated hemoglobin (HbA1c) was 8.3%. The most commonly prescribed antidiabetic medication was metformin (87.71%), while lipid lowering therapy was atorvastatin (77.79%). Conclusions: This study on newly diagnosed T2DM patients with dyslipidemia found that majority of the patients had hypertriglyceridemia, family history of diabetes and were physically inactive. More than half of T2DM patients were either overweight or obese. More than 2/3rd of the patients had mixed dyslipidemia. Statins were prescribed to the majority of these patients and atorvastatin was the most commonly prescribed statin in Indian T2DM patients with dyslipidemia.